KONTRADIKSI DUA SUMBER HUKUM UTAMA DIALEKTIKA HADITS AHAD DAN QIYAS - Silahuddin, Muhammad (An Nawawi, 2021)
This article shows that even though the Sunnah/Hadîts and qiyâs has been agreed by four priests schools (al-a’immat al-arba‘ah) as a source of Islamic law (mashâdir al-Ahkam), in addition to the Qur’an and ijmâ‘, but occurs deviation between them and their followers in the event of a contradiction (ta‘ârudh) between hadits al-âhâd with qiyâs, in the case used as the arguments to establish Shari'ah/Islamic Law. The majority of scholars, agreed to prioritize hadits al-âhâd than qiyâs as legal proof, the condition strict, ie that hadits al-âhâd to be authentic. Added by Hanafiyah, hadits al-âhâd is not associated with things that can not be avoided (‘umûm al-balwâ), and not unlike the practice of narrators, and not in conflict with the Qur’an and/or hadîts mutâwatir. Added by Imam Malik and scholars Malikiyah, the hadits al-âhâd does not contradict with ‘Amal Ahl al-Madînah, because of the nature of its legal force as the force of law hadîts mutâwatir. However, in certain contexts, Imam Malik put hadits al-âhâd than qiyâs in 4 (four) problems, namely the hadîts about: something/dog licking the affected vessel, musharrâh system purchase, sale and purchase of the system of ‘Arâyah, and about qur’ah. Similarly, imam Malik put qiyâs than hadits al-âhâd in matters of eating and drinking at the time of fasting due to forget, is a legal void, making it obligatory to be fullfilment (qadhâ’). While the opinion of the Hanafi imams who pioneered and Syafii instead basing on hadits al-âhâd narrated by Abu Hurayrah, that the fast is not invalidated, so it should be forwarded (enhanced), and not obligatory to be fullfilment (qadhâ’). Keywords: hadits al-âhâd, qiyâs, ta‘arudh, istinbâth, al-madzâhib al-arba’ah.